2011
DOI: 10.1136/sti.2010.046441
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bacterial vaginosis on the response to Trichomonas vaginalis treatment among HIV-infected women

Abstract: Objective Trichomonas vaginalis (TV) is common in HIV+ women, and host factors may play a role in TV treatment outcomes. The purpose of this study was to examine the influence of bacterial vaginosis (BV) on the response to TV treatment among HIV+ women. Methods A secondary analysis was conducted of a clinical trial which randomised HIV+/TV+ women to metronidazole (MTZ) treatment: 2 g (single-dose) versus 7 day 500 mg twice daily (multidose). BV was classified using Nugent scores from baseline Gram stains. Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
2
21
1
Order By: Relevance
“…e association between BV and trichomoniasis is frequent in HIV-infected patients, and it may bring difficulties to the treatment of both diseases [23,24]. In the present study, 53.8% of patients with trichomoniasis also showed BV, with 28.6% of recurrence for both infections, which is in agreement with those authors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…e association between BV and trichomoniasis is frequent in HIV-infected patients, and it may bring difficulties to the treatment of both diseases [23,24]. In the present study, 53.8% of patients with trichomoniasis also showed BV, with 28.6% of recurrence for both infections, which is in agreement with those authors.…”
Section: Discussionsupporting
confidence: 82%
“…Trichomoniasis favors the occurrence of BV [23], and coinfection with the two microorganisms may hinder the treatment of both diseases in HIV-infected patients [24]. BV causes cellular alterations in the cervix [25], and similarly to trichomoniasis, favors the acquisition of human papillomavirus (HPV) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Kissinger et al 35 found that the 2-g single dose of MTZ for the treatment of TV infection in HIV-positive women was less effective than the 7-day twice-daily 500-mg dose, but that this treatment effect was only found among women with BV. 59 Balkus et al 13 found similar findings in a cohort of African sex workers. Furthermore, both of these studies found that ART also seemed to interfere with MTZ treatment of TV.…”
Section: Discussionmentioning
confidence: 52%
“…In their study of HIV outpatient clinic attenders, Gatski and colleagues found a high rate of bacterial vaginosis (67%, 163/244) in HIV positive, mainly African American women infected with Trichomonas vaginalis (TV) 1. We recently conducted a pilot study to test for TV in 183 stored self-taken vaginal samples from multiethnic female London students who took part in the prevention of pelvic infection chlamydia screening trial 2.…”
mentioning
confidence: 99%
“…As Gatski and colleagues point out,1 TV is important because it is associated with genital HIV shedding in HIV positive women, and this can be reduced by effective TV treatment. There are no data on the prevalence of TV in young women in the community in the UK 6…”
mentioning
confidence: 99%